Economic evaluation of a small wastewater treatment plant under different design and operation scenarios by life cycle costing. (2022) - Pryce, David; Kapelan, Zoran; Memon, Fayyaz A.
Abstract: High-performance wastewater treatment technologies suited to the urban environment remain largely inaccessible to developing countries due to financial constraints. Instead, inadequate technologies are being used that adversely affect the quality of water resources and limit their sustainability. One high performing technology that offers possible solution is a packaged version of the integrated fixed-film activated sludge (IFAS) system consisting of a 20 m 3 aerobic reactor and a 4.2 m 3 settlement tank. The present work has investigated aspects of this typically-expensive solution that can be economized to improve its uptake in these countries. To achieve this a life cycle cost analysis (LCCA) was performed and potential savings identified. The results obtained show that the life cycle cost is 0.31/m 3 and that costs primarily occurred at the construction stage (11.9%) and the operation and maintenance stage (88.1%) with negligible disposal costs. A reduction of up to 42.4% in construction costs were shown to be accessible by adopting other materials such as high-density polyethylene (HDPE) or to a lesser extent glass-fibre reinforced polymer (GFRP). The greatest single cost in the life cycle was found to be incurred by aeration (48.9%), requiring expenditure of 0.15/m 3, however the use of intermittent aeration (IA) could reduce this further to 0.08/m 3 . Further work is suggested to investigate the broader sustainability of the different aeration strategies in light of these economic results. Highlights: Life cycle costing a package integrated fixed-film activated sludge (IFAS) system. Total cost of wastewater treatment by IFAS over 15 years calculated as 0.31/m 3 . Stainless steel is the most expensive tank construction material investigated. Intermittent aeration offers substantial economic savings compared to continuous. The costs of further enhancing total nitrogen removal are calculated as 17, 710.